(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
Following an acute physical exercise, both post-activation potentiation and fatigue of the neuromuscular apparatus may occur. The voluntary recruitment of motor units occurs with frequencies that elicit incompletely fused tetanic contractions and these frequencies are most susceptible for post-activation potentiation as well as low-frequency fatigue. Therefore, the goal of the present study was to investigate which of the processes post-activation potentiation or low-frequency fatigue will be prevalent after 5 s maximal voluntary contraction (MVC). Eight healthy untrained men (age 24—35 years, mass 81.2 ± 5.1 kg) performed maximal sustained isometric knee extension for 5 s at a knee angle of 90 degrees. The contractile properties of quadriceps muscle evoked by electrical stimulation at 1, 7, 10, 15, 20, 50 Hz and 100 Hz, were recorded before and immediately after the exercise and 3, 5, and 10 min following the exercise. The rest interval between muscle electrical stimulation was 3 s. A significant raise of force evoked by 1—15 Hz stimulation was observed immediately after the 5 s MVC exercise (p < 0.01). Later in recovery (at 10 min) the contraction force at 15 Hz and 20 Hz significantly decreased (p < 0.05). Tetanic force at 50 Hz and 100 Hz demonstrated a significant decrease immediately after the exercise and remained depressed up to 3 min (p < 0.01). The ratio of 20 / 50 Hz recorded immediately after the 5 s MVC increased significantly (p < 0.05), however 10 min after the exercise there was a significant decrease compared to its initial level (p < 0.05). The simultaneous occurrence of post-activation potentiation at low stimulation frequencies and suppressed forces at high stimulation frequencies suggests that potentiation and fatigue mechanisms were acting concurrently. Moreover, when post-activation potentiation is lost (in 10 min after the 5 s MVC exercise), the contraction force at low stimulation frequencies decreases resulting in significant low-frequency fatigue. Keywords: isometric exercise, electrical stimulation, low-frequency fatigue, recovery.